(untitled) (Research, Society and Development, 2021)
Ice creams have great acceptance and demand by consumers around the world. They are foods obtained through an emulsion of fats and proteins, these ingredients if stored or handled incorrectly can be the source of multiplication of several microorganisms. This work focuses on the microbiological analysis of artesanal and industrial ice cream in two times of the year (winter and summer), performed using the methodology adapted from Silva et al (2010) and the legislative microbiological standards used from RDC No 12 from Anvisa (Brasil, 2001). The main focus was the detection of microorganisms of importance in the food industry, as they are precursors of foodborne diseases epidemics, such as Escherichia Coli, Salmonella, total coliforms, thermotolerant coliforms, molds, yeasts and aerobic mesophilic bacteria. It was observed in the analysis results that all 30 samples showed growth of aerobic mesophilic bacteria, molds and yeasts, that only four (13.33%) did not have total coliforms and none had Salmonella. There was no great difference between the results of the analyzes of samples collected in the summer and winter, the level of contamination in general was high in samples from both seasons.